Main failure mode of oil-air lubricated rolling bearing installed in high speed machining. (August 2017) - Chang, Zhou; Jia, Qian; Yuan, Xing; Chen, Yaolong
Abstract: The failure mode of rolling bearings is closely related to its operating conditions. In this study, a batch of rolling bearings, which have failed after a certain service period under oil-air lubrication, were collected and the failure modes of the bearings were analyzed. A statistical analysis showed that abrasion and not fatigue is the main failure mode of the collected bearings. The main failure mode for the inner and outer rings of rolling bearings in oil-air lubrication was abrasion, burn-up, corrosion, fatigue and indentation respectively. The causes of abrasion, burn-up, fatigue, indentation and corrosion failure mode were analyzed by visual inspection and the elemental composition of the raceway material of the failed bearings was analyzed by energy-dispersive X-ray spectroscopy. The domination of abrasion failure mode in rolling bearing under oil-air lubrication might be due to the existence of haze particles in the lubrication air. Highlights: A batch of rolling bearings, which have failed after a certain service period under oil-air lubrication, were collected from maintenance shops. A statistical analysis showed that abrasion and not fatigue is the main failure mode of the collect bearings. The results of the EDS analysis indicate that the haze particles are the main cause of abrasive wear.